Orchids smarter than scientists: an approach to Oncidiinae (Orchidaceae) taxonomy - Dalström, Stig (Universidad de Costa Rica, 2016)
When initiating a project in plant taxonomy it is necessary to carefully examine the type specimen for each taxon that has been described. Just as important, however, is to explore the natural habitats of the plants because that is where the dynamics occur, which is the logical source for the necessary data.